Working from home : making the new normal work for you - Mangia, Karen, 1975- (John Wiley & Sons, Inc., 2020)
"From setting up your virtual office, to time management, to dealing with conference call fatigue, turn remote work into a career powerhouse--even if you live in an apartment. This book has everything you need to know to make the most out of working from home in the new normal so that you and your organization can thrive in a socially-isolated world. Learn how to claim your space, create your environment, and make your career virtually vital without ever entering an office building. With this book, you'll see how to reimagine your career, realign with your team, and create influence for yourself and others. Working from Home addresses top-of-mind topics: What does collaboration mean now? How can you make sure that your career is neither out of sight nor out of mind even though you're not going into an office? How to connect on a regular cadence and gain valuable input for projects and new initiatives. Don't Become a ZOOM Zombie: self-care strategies for productivity, sanity, and adaptation to the new normal. Adaptation and adoption: how to gain consensus and drive culture, even when everyone is remote. What leaders need to know about old-school strategies in a new world order: how to inspire teams even when you can't be in the same room"--